2021
DOI: 10.1155/2021/7762127
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of Structural and Residual Trapping Phenomena during CO2 Sequestration in Deccan Volcanic Province of the Saurashtra Region, Gujarat

Abstract: This work aims to study the structural and residual trapping mechanisms on the Deccan traps topography to elucidate the possible implementation of CO2 geological sequestration. This study provides an insight into a selection of stairsteps landscape from Deccan traps in the Saurashtra region, Gujarat, India. Various parameters affect the efficiency of the structural and residual trapping mechanisms. Thus, the parametric study is conducted on the modeled synthetic geological domain by considering the suitable in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Thus, we anticipate that the peak passive degassing is toward the end of stage 1 coincident with increasing surface eruptions. In addition, the increased presence of surface basaltic lava flows in Stage 2 may sequester degassed Deccan CO 2 instead of atmospheric emission (Clark et al., 2020; A. Kumar & Shrivastava, 2020; Punnam et al., 2021; Schwartz, 2020; Snæbjörnsdóttir et al., 2018). This physical mechanism (suggested in Sprain et al., 2019 and Nava et al., 2021) thus provides a natural explanation for the observed pre‐K‐Pg global warming observed in a various marine and terrestrial paleo‐proxy records (Hull et al., 2020) which is co‐incident with the eruption of the Kalsubai sub‐group (Schoene et al., 2019; Sprain et al., 2019).…”
Section: New Conceptual Model For Cfb Magmatic Systemmentioning
confidence: 99%
“…Thus, we anticipate that the peak passive degassing is toward the end of stage 1 coincident with increasing surface eruptions. In addition, the increased presence of surface basaltic lava flows in Stage 2 may sequester degassed Deccan CO 2 instead of atmospheric emission (Clark et al., 2020; A. Kumar & Shrivastava, 2020; Punnam et al., 2021; Schwartz, 2020; Snæbjörnsdóttir et al., 2018). This physical mechanism (suggested in Sprain et al., 2019 and Nava et al., 2021) thus provides a natural explanation for the observed pre‐K‐Pg global warming observed in a various marine and terrestrial paleo‐proxy records (Hull et al., 2020) which is co‐incident with the eruption of the Kalsubai sub‐group (Schoene et al., 2019; Sprain et al., 2019).…”
Section: New Conceptual Model For Cfb Magmatic Systemmentioning
confidence: 99%
“…The previous study on the influences of geological folds has shown their impacts on the primary trapping mechanisms and sweeping efficiency of CO 2 plume for different ranges of perturbed subsurface morphology [42]. The existence of geological structures like anticline and syncline can certainly control the CO 2 migration, lateral spreading, and safe storage of CO 2 in the domain [12]. Figure 1 gives a glimpse and schematic explanation of the simulation analysis carried out in the current research study.…”
Section: Introductionmentioning
confidence: 82%
“…The structural and residual trapping is calculated using the equation illustrated in Table 1 Eq. ( 11)- (12). The movable plume is the remaining quantity of CO 2 after the structural and residual trapping.…”
Section: Estimation Of Structural Residual and Solubilitymentioning
confidence: 99%
See 2 more Smart Citations